Interview of Alan H. Shapley by Brian Shoemaker - Shapley, Alan H. (Byrd Polar Research Center Archival Program, 2008)
Key Names Appleton, Sir Edward, Nobel prize winner for ionospheric discoveries, p. 5 Audeshaw, Hugh, major leader of IGY in Antarctica, pp. 15-18, 24-25 Crary, Bert, pp. 27-28 Berkner, Lloyd, major leader of IGY and Antarctic expedition, pp. 4-6, 10-11, 27 CRPL, Central Radio Propagation Laboratory, pp. 1-2 Dufek, Admiral George, pp. 19, 24 Gould, Larry, pp. 11-12, 18-19 Kaplan, Joseph, Chair of the US Committee for the IGY, pp. 8 Seaton, Stewart, first Director of Geophysical Institute, Fairbanks, Alaska, p. 2 Van Allen, James, physicist, p. 4 Waterman, Allan, Director of the National Science Foundation, pp. 16-17 Wexler, Harry, Chief Scientist for the Antarctic Program, pp. 12-13, 30 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Alan_Shapley_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Alan_Shapley_2.mp3 Dr. Alan Shapley began his long polar career in Alaska, where he worked for several years during the late 1940’s on ionospheric and radio research at the Central Radio Propagation Laboratory (CRPL) in Anchorage. He also spent time in Washington, D.C. with the newly created Geophysical Institute. His duties required various trips by C-46’s in Alaska, including Fairbanks, Barrow, Anchorage, and the Aleutian Islands. In 1949 Lloyd Berkner, James Van Allen, and others advocated establishment of another Polar Geophysical Year in 1957-58. The First Polar Year was in 1882-83; the Second Polar Year in 1932-33. Given the major scientific advances of more recent years, especially during WWII, it seemed reasonable to begin soliciting support from various international scientific organizations for a Third Polar Year. But soon the plans expanded from a primarily Polar emphasis to a much more broadly conceived global scientific enterprise. Thus the International Geophysical Year (IGY) was born. Among the disciplines included were geomagnetism, cosmic rays, solar activity, the ionosphere, seismology, gravity, and ...